Evaluation of preformulation and formulation parameters of an antistress herbal capsule. - NASREEN. S; DR.&.&ARAYA&A& (International Journal of Pharma and Bio Sciences, 2011)
The formulated capsule is a bi-herbal preparation recommended as antistress agent. It contains Withania somnifera and Tinospora cordifolia in equal proportions. The present work is based on the standardization of individual ingredients and formulation of the capsule with improved formulation parameters. Physicochemical parameters were also checked for individual crude drugs and finished capsules like ash value, extractive value, and loss on drying. Granulation was done by using starch (20 % solution) as binder by wet granulation technique. The preformulation parameters like bulk density, tap density, Carr’s index, Hausner’s ratio and angle of repose were checked for laboratory granules. The granules were capsulated and the designed formulations were evaluated for content uniformity, weight variation and disintegration time. Quantification for Withaferin-A and Berberine of the finished formulation was done by HPLC method. The designed formulation was in conformity to the properties evaluated for the capsules and further preclinical studies have to be done to test its efficacy.